Bargaining and gender relations: within and beyond the household - Agarwal, Bina (International Food Policy Research Institute, 1997)
Most discussions on bargaining also say little about gender relations beyond the household, and about the links between extrahousehold and intrahousehold bargaining power. This paper spells out the nature of these complexities and their importance in determining the outcomes of intrahousehold dynamics. It also extends the bargaining approach beyond the household to the interlinked arenas of the market, the community, and the State.